Genome-wide identification and analysis of the IQM gene family in soybean - Lv, Tianxiao; Liu, Qiongrui; Xiao, Hong; Fan, Tian; Zhou, Yuping; Wang, Jinxing; Tian, Chang-en (Frontiers in Plant Science, 2023)
IQM, a plant-specific calmodulin-binding protein, plays multiple roles in plant growth and development. Although a comprehensive analysis has been carried out on the IQM family genes in Arabidopsis and rice, the number and function of IQM genes in other species have not been explored. In this study, we identified 15 members of the soybean IQM gene family using BLASTP tools. These members were distributed on 12 soybean chromosomes and constitute six pairs caused by fragment duplication events. According to phylogeny, the 15 genes were divided into three subfamilies (I, II, and III), and members of the same subfamily had similar gene and protein structures. Yeast two-hybrid experiments revealed that the IQ motif is critical for the binding of GmIQM proteins to GmCaM, and its function is conserved in soybean, Arabidopsis, and rice. Based on real-time PCR, the soybean IQM genes were strongly induced by PEG and NaCl, suggesting their important biological functions in abiotic stress responses. Overall, this genome-wide analysis of the soybean IQM gene family lays a solid theoretical foundation for further research on the functions of GmIQM genes and could serve as a reference for the improvement and breeding of soybean stress resistance traits.